PENGARUH IKLIM ORGANISASI, KOMUNIKASI INTERPERSONAL DAN KEPUASAN KERJA TERHADAP KINERJA - Faisal, Ahmad; Istiyah, Istiyah (Feb Universitas Dirgantara Marsekal Suryadarma, 2018)
This study aims to find out about the influence between Organizational Climate, Interpersonal Communication and Job Satisfaction on the performance of NCO / Tamtama in Kodiklatau. Data derived from questionnaires distributed were analyzed data, among others: description of data, testing of research requirements, including: normality test, homogeneity test, and linearity test. To prove the influence of Organizational Climate variable (X1), Interpersonal Communication (X2) and Job Satisfaction (X3) on Performance (Y). In this research, used data analysis technique with path analysis. Based on the results of the research analysis: 1) There is influence Organizational Climate (X1) on Job Satisfaction (X3) of 0.175; 2) There is the influence of Interpersonal Communication (X2) on Job Satisfaction (X3) of 0.35; 3) There is an effect of Organizational Climate (X1) on Performance (Y) of 0.293; 4) There is the influence of Interpersonal Communication (X2) on Performance (Y) of 0.259; 5) There is influence of Job Satisfaction (X3) on Performance (Y) of 0.254. Keywords: Organizational Climate, Interpersonal Communication, Job Satisfaction and Performance